ISTILAH-ISTILAH PENGGUNAAN BAHASA PADA TRANSAKSI JUAL BELI ONLINE (ONLINE SHOP) DI AKUN MEDIA SOSIAL - Ridhaningtyas Wahyu; Revasya Gewani (CARAKA, 2022)
The use of language in society cannot be separated from the times, motivated by advances in technology and communication as well as the emergence of social media applications that can be used for free by the community, so that it is widely used by the community as a means of product marketing. One form of this development is the convenience of shopping, namely online shopping. Regarding the use of language, there are several distinctive languages ​​or registers that appear in the context of buying and selling online. This peculiarity is supported by a number of things, from the form of online shop language terms and their use functions. The subject of this research is the utterances of sellers and buyers that appear during the online buying and selling process. Some of the peculiarities of the data are obtained by listening to online transactions on a number of sites or social media accounts. Keywords: online buying and selling, registering, language use.